Pellagra induced psychosis: a rare presentation - Parikh, Disha; Panse, Smita (International Journal of Research in Medical Sciences, 2019)
Pellagra is a nutritional deficiency disease associated with low levels of niacin (vitamin B3). Neuropsychiatric symptoms are rare and are difficult to be diagnosed by clinicians in a timely manner. A 35 years old male was brought with complaints of generalized weakness, decreased appetite and work impairment since past 4 years. Scaly and itching skin rashes have also been present since 3 months followed by hearing voices, suspiciousness and agitated behaviour since one month. On examination, he had pruritic skin rashes over hands which extended over face and neck. His diet comprised mainly of jowar and maize and had history of occasional alcohol use. With an initial diagnosis of psychosis, the patient was started on oral olanzapine. Laboratory and imaging investigations were within normal limits. Dermatology referral confirmed pellagra clinically. The patient was started on injectable multivitamins for 14 days and later shifted to oral multivitamins. Patient showed significant improvement in his skin and neuropsychiatric symptoms. Present case suggests that physicians need to remain vigilant because it is easy to overlook such patients. Pellagra has an insidious onset and psychiatric symptoms appear rare and late in the course when disease is allowed to progress.